Evaluation of soil carbon characteristics under different planting patterns on sloping farmland in the hilly and gully region of the loess plateau - Panpan Zhang; Yang Zhang; Zenghui Sun (Scientific Reports)
Abstract A six-year field experiment was conducted in the Loess Plateau to explore the impacts of five planting patterns, namely fallow(C0), continuous maize cropping(C1), continuous alfalfa cropping(C2), maize-sorghum-sorghum-millet (cereal) rotation(C3), and kidney bean-sorghum-sorghum-millet (legume-cereal) rotation(C4), on different forms of soil carbon. The results showed that, compared with the C0 pattern, long-term continuous cropping or rotation of different crops significantly increased the mass fractions of various forms of carbon in the 0–40 cm soil layer. Specifically, the total carbon increased by 57.11 − 122.52%, the organic carbon increased by 81.93 − 244.12%, the inorganic carbon mass fraction increased by 29.52 − 39.25%, and the light fraction organic carbon showed the most prominent increase, being 3–11 times that of the C0 pattern. In the soil layers from 0 to 15 cm, there were differences among different planting patterns. Under the C2 pattern, the mass fractions of soil total carbon, organic carbon, and light-fraction organic carbon were the highest, followed by those under the C3 and C4 patterns, while those under the C1 pattern were relatively low. The performance of inorganic carbon was different. The C2 pattern only increased the inorganic carbon content in the 0–5 cm soil layer. As the soil depth increased, the contents of various types of carbon decreased, and the decrease rate of C2 were the largest. In summary, long-term continuous alfalfa cropping is an effective approach to increasing soil carbon in dry lands, especially organic carbon and light fraction organic carbon. However, this effect is mainly concentrated in the surface soil above 15 cm. When comparing continuous cropping and rotation, rotation has a stronger effect on increasing soil carbon content than continuous cropping, and there is no significant difference in the impact on soil carbon content among different rotation patterns.